PREPARATION OF DIGITAL TEACHING MATERIALS ACCOUNTING FOR SERVICE, TRADE AND MANUFACTURING COMPANIES FOR CLASS XII SEMESTER 2 SMK NEGERI 1 TANJUNG PINANG - Serly Serly; Natalia Christina (ConCEPt - Conference on Community Engagement Project, 2022)
The Covid-19 pandemic has caused several changes to the learning methods applied by all educational institutions. Changes in learning methods adapted to pandemic conditions caused several problems in the teaching and learning process in schools. The problem experienced by SMK Negeri 1 Tanjung Pinang is that there is limited time for the school to compile digital teaching materials and thus it affects teaching and learning activities carried out by the school. Therefore, this community service project is carried out with the aim of producing outputs in the form of modules, question banks, powerpoints and learning videos for the subject of Accounting for Service, Trade, and Manufacturing Companies for class XII semester 2. The preparation of digital teaching materials is carried out through the science and technology diffusion method, interviews with schools parties as well as literature references that is matched to the School's Core Competencies and Basic Competencies (KIKD). The implementation of the digital teaching materials will be carried out in the 2nd semester of class XII starting in 2022. Digital teaching materials that have been designed are expected to help the school to improve the efficiency and effectiveness of the teaching and learning activities carried out. This project is expected to be a reference for the next project implemented with the scope is in the school and it is hoped that the resulting output will be more varied.